The relationship between dimensions of employee engagement and employee performance / Siti Sara Azhari - Azhari, Siti Sara (Faculty of Business and Management, 2017)
Employee engagement has received vast attention from employees, management, and even researchers for the past 10 years (Bedarkar and Pandita, 2013). Employees today are more desire for positive feelings about their work experiences that go beyond global attitude of job satisfaction and commitment (Shuck, 2010). Employees who are properly engaged and managed can be considered as esteemed assets and they can become competitive advantages to the organization as people are difficult to imitate (Anitha, 2014). Besides, employees who are engaged are commonly come to work feeling more connected to the organization, performing their work with high level of enthusiasm and have high level of production There are also studies found that employees who are engaged stay with their organization longer, reduced the rate of turnover, and consequently help the organization to save recruitment and retraining costs (Shuck, 2010). Furthermore, there is a study found that engaged employees affect the experience of customers and co-workers. Engaged employees also tend to put high trust on management, and more focus on mission attainment, strategic direction, and organizational outcome. Therefore, many employees turning toward human resource researchers and practitioners to develop and support strategies that facilitate engagement-encouragement cultures as there are immense number of advantages of engaged employees (Shuck, 2010). Even though there are high number of studies that have been conducted to test the effect of employee engagement, there is a need to study how the dimensions of employee engagement have impacts on employees’ performance, particularly in companies is Malaysia. Thus, this study examined the relationship between three dimensions of employee engagement, namely leadership, work environment, and communication and employees’ performance. The study covered a sample of 175 employees from 300 employees of TNB Research Sdn. Bhd. The sample was selected through convenient sampling technique. Primary data are used in this study through the development of questionnaires.